Phenotypic plasticity in Pinus canariensis seedlings growing at chilling and freezing temperatures - José Carlos Miranda; José Carlos Miranda; Unai López de Heredia; Victoria Fernández; Pilar Pita; Pilar Pita (Frontiers in Forests and Global Change, 2023)
Global change is affecting the frequency and temporal distribution of frost events. We can expect damage caused by low temperatures to increase specially at the upper limit of a species’ elevation range. Here, we assessed how Pinus canariensis two-year old seedlings from different islands and elevations responded differently to chilling and freezing temperatures. Seedlings from six populations were grown either in a greenhouse (tmin = 5 ̊C, chilling conditions) or outdoors (tmin = −3.3 ̊C, freezing conditions) for 104 days in winter. Seedlings from one of these populations belonged to three half-sib families. Maximum quantum yield of Photosystem II and evapotranspiration (ETP) were determined four times throughout the study. All populations suffered photoinhibition under freezing but not under chilling conditions. We measured the lowest ETP in the population from the warmest and driest environment and lowest elevation (250 m) both under chilling and freezing conditions. The three populations from the higher elevations reached the highest ETP under chilling, a likely adaptation to the shortening of the vegetative period. The effect of elevation remained elusive for other parameters, which could be partly attributed to high intrapopulation variability. Epicuticular wax concentration increased and needle water content decreased in plants growing outdoors. All populations except the one most affected by cold dehydration showed osmotic adjustment and a simultaneous decrease in tissue elasticity under freezing. This response was stronger in the population from the highest elevation (2,241 m). Our results highlight the coexistence of adaptive processes, genetic variation and plasticity conditioning the response to low temperatures in this species.